Historical aspects that culminated in the indiscriminate use of pesticides (Research, Society and Development, 2020)
Pesticides are chemical substances with biocidal characteristics, encompassing physical, chemical or biological aspects, used in the fields of agricultural crops. The coexistence of benefits and harmful effects is a challenge today concerning the protection of ecosystems and human health. In this perspective, this research made a survey of data, with the general objective of investigating the reasons that trigger the indiscriminate use of pesticides and the obstacles that the rural producers find for not carrying out a sustainable agriculture. As a methodological characteristic, it is a narrative review, through a search in national databases focused on the health area, being carried out between the months of August and October 2020, through a search in reliable databases aimed at respective theme. As results and discussion, the following sources were consulted: academic articles, monographs, websites and books. Through this research, it is concluded that historical factors linked: to the needs of the post-war (First and Second World War) aimed at the low food supply; the policy of the Green Revolution; rural exodus; ineffective inspection of pesticide products; laws not put into practice; culminated today in the indiscriminate use of pesticides. It is also worth mentioning that countless factors are contributing to the increased use of pesticides, such as the introduction of seed species in places without natural enemies; genetic changes in plants, making them more sensitive to some pests; ecological imbalances; and inadequate storage methods.